Evaluation of testosterone and prolactin hormones levels in erectile dysfunction patients after single oral dose of Tadalafil - Hayder Hamed Abed (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2008)
Erectile dysfunction (ED) is defined as a consistent inability to sustain an erection sufficient for sexual intercourse. Tadalafil is a selective, reversible inhibitor of cyclic guanosine monophosphate (cGMP)-specific phosphodiesterase type 5 (PDE5). When sexual stimulation causes the local release of nitric oxide, inhibition of PDE5 by tadalafil produces increased levels of cGMP in the corpus cavernosum. This results in smooth muscle relaxation and inflow of blood into the penile tissues, thereby producing an erection. Tadalafil has no effect in the absence of sexual stimulation. Erection dysfunction could attribute abnormal levels of testosterone and prolactin levels.